PERSPECTIVES ON WATER MANAGEMENT FROM LOCAL WATER DECISION MAKERS IN A COASTAL REGION - Bunnell, Anne E (East Carolina University, 2023)
The effects of climate change are already apparent in eastern North Carolina. Higher than average global temperatures have been implicated in more extreme weather events, with more frequent and intense storms and prolonged periods without precipitation. Some of the impacts include flooding, droughts, and wildfires and each has caused loss of property and life, leading to economic and social consequences. Community water suppliers who are responsible for protecting public health and well-being are on the front lines of transitioning their communities to greater climate resiliency. Agencies at the federal level are developing case studies and training materials to assist in these transitions. However, beyond knowing the job titles that are held by individuals in local government and in utilities, this population of local water decision makers is under-investigated (Cockerill, 2014). This study employed a mixed methods approach of key informant interviews and a survey sent to a broader, representative population of these individuals to gather critical details to elucidate their priorities and provide avenues through which to reach them.
Keywords: water resource management; local water decision makers; coastal region; public water supplies; demand side management; CCPCUA; Municipal water supply--North Carolina--Outer Banks--Management; Climatic changes--North Carolina--Outer Banks; Public health administration--North Carolina--Outer Banks